Metabolite profiling, lignin accumulation and gene expression of oil palm germinated seed treated with Hendersonia GanoEF1 - Ismail, Muhammad Faiz (2019)
Oil palm (Elaeis guineensis Jacq.) is considered as a golden crop and also one of the main contributors to economy of Malaysia. Unfortunately, basal stem rot (BSR) disease remains as a major obstacle in oil palm cultivation and production in Malaysia. The uses of biocontrol agents become the main attention to control and suppress the plant disease. The objective of this study is to compare the metabolite profiling, lignin accumulation and gene expression of root of oil palm germinated seed treated with Hendersonia toruloidea (GanoEF1) and Ganoderma boninense. Endophytic fungi Hendersonia GanoEF1 was obtained from GanoDROP Unit (MPOB) Kajang, Selangor. Four hundred and fifty oil palm germinated seed were used and arranged randomly by using completely randomized design (CRD). The experiment conducted using four-week-old oil palm germinated seed with five following treatments; germinated seed control untreated and uninfected with G. boninense (TC), germinated seed treated Hendersonia GanoEF1 (TH), germinated seed infected G. boninense (TG), germinated seed treated Hendersonia GanoEF1 and infected with G. boninense (THG), and germinated seed control with uninfected rubber wood block, RWB (TB). Methanol extraction methods were used for metabolite profile analysis. Sixty five compounds from different treatments were selected as main compounds. Three types of sterols detected from these treatments such as β-sitosterol, Stigmasterol and Campesterol were used as a potential indicator to detect the present of pathogen (stress) in plant. Using the Venn-digram, few compounds have been identified and used to detect the present of G. boninense and Hendersonia GanoEF1 in oil palm roots were: Methyl 6-0-[1-methylpropyl]-β-D-galactopyranoside; Hexadecanoic acid, methyl ester; Tetradecanoic acid and 9,12-Octadecadienoic acid (Z,Z)-, 2-hydroxy-1-(hydroxymethyl)ethyl ester. Determination of lignin accumulation and total lignin content in oil palm root is one of the potential methods to indicate the level of plant‘s stress. Two cm above the root tips were cut to determine the lignin accumulation whereas for total lignin content, 100 mg of root were used to compare the acid-soluble and acid- insoluble lignin between the treatments. Highest thickness of lignin was found in treatment TG (82.65 ± 2.98) and the lowest in treatment TC (61.11 ± 1.05). For total lignin content, treatment TC shows the highest (263.73 ± 22.52) and the lowest found in treatment TG (188.43 ± 7.42). Study the gene expression of plant defence-related enzymes which are superoxide dismutase (SOD) and catalase (CAT) is also one of the method that possibily used to indicate the stress level in plant. Highest SOD level was found in treatment TC (24.56 ± 0.12) and lowest in treatment THG (23.49 ± 0.19) whereas highest CAT found in treatment THG (17.62 ± 0.06) and lowest in treatment TC (16.98 ± 0.19). This study revealed that Hendersonia GanoEF1 is suitable as an effective biological control agent for promoting the growth of oil palm seedlings and controlling BSR disease.